The role of grain and twin boundaries on discontinuous precipitation of Mg17Al12 phase in Mg-Al alloy - Yi Wang; Fei Guo; Luyao Jiang; Hang Yu; Gege Wang; Congren Shen; Zhongwei Wang; Linjiang Chai; Yanlong Ma (Journal of Magnesium and Alloys)
Mechanism of discontinuous precipitation (DP) in AZ80 alloy was investigated by phase-orientation correlated characterization. The results show DPs nucleate by turning the original grain boundaries (GBs) as reaction front (RF), and further driving the RF to realize their growth. The DPs regions retained the same orientations as their parent grains. The misorientation angle and rotation axis of RFs had strong influence on DPs nucleation. The low-angle GBs, twin boundaries (TBs) and the GBs with specific misorientation axis which are known as low energy and low mobility GBs can hardly initiate DPs. In addition, the TBs had a strong ability to inhibit the growth of DPs, but it should be noticed that the growth of DPs cannot be totally inhibited by TBs. DPs can engulf the twins when the growth direction is approximately parallel to the long axis of TBs. The inhibition behavior is related to the distribution of Al solute atoms near the RF, boundary interactions of the TBs and twin tips with the RF, and the morphology of the continuous precipitations within the twins.